Students' Strategy In consecutive Interpreting a Short Motivation Speech into Bahasa Indonesia - Reva Afrina; Havid Ardi (Universitas Negeri Padang, 2021)
This research aims to find out the strategies that were used by low, medium, and high-level students English Department of Universitas Negeri Padang in interpreting an English short speech into Bahasa Indonesia consecutively. The subject of this research was the third-year students of English Department who had taken English-Indonesia interpreting class. The sample was 23% were chosen out of 53 students by random sampling technique. The data were collected using an interpreting test consecutively via zoom meeting. The results show that the dominant strategy used by low-level students was the skipping strategy it was about 49 times used by the students during the test, it means (33.8%) out of the students used this strategy. Then, the dominant strategy was used by medium level students was skipping 29 times used by the students during the test or (20.86%) out of the students. Last, students in high level dominant used explicitation strategy 41 times used by the students during the interpreting test or (28.87%) out of the students. It could be concluded that students find it difficult to comprehend the source language; it proves that students skip the SL 86 times during the interpreting test, which was about 20.67%. Students in the low and medium level tend to use the skipping strategy, but students in the high level tend to repair and make the interpretation clearly by using explicitation strategy.